Demokrasi di Dunia Arab dalam Akun Instagram @hajjaj_cartoons (Analisis Semiotika Saussure) - Umi Kulsum (Universitas Muhammadiyah Gorontalo, 2025)
This research aims to analyze the meaning of caricature as a medium of political expression related to democracy in the Arab World through Ferdinand de Saussure's semiotic approach, specifically the theory of signifier and signified. The background of this research is the complexity of democratic systems in Arab countries that are mostly led by authoritarian regimes, with Jordan as a case study that combines a constitutional monarchy system with elements of representative democracy. The research data is obtained from caricatures uploaded on the Instagram account @hajjaj_cartoons, which reflect the condition of democracy through visual symbols. The method used is qualitative, with in-depth analysis of the visual elements and the socio-political context behind the caricatures. This research is expected to provide new insights into the way caricatures represent criticism of the democratic system in the Arab World. The results show that caricatures depict Arab democracy in Jordan as a mere formality, especially in organizing parliamentary elections. This research also shows how caricatures serve as an effective tool to convey social criticism and raise public awareness about the importance of transparency and fairness in Arab democratic practices.